2006
DOI: 10.1111/j.1399-3038.2006.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

927T>C polymorphism of the cysteinyl‐leukotriene type‐1 receptor (CYSLTR1) gene in children with asthma and atopic dermatitis

Abstract: Asthma and atopic dermatitis share several common features and Cysteinyl-leukotrienes are mediators that participate in the pathogenesis of both diseases. Recently, a new polymorphism (927T>C) has been identified in cysteinyl-leukotriene type-1 receptor (CYSLTR1) gene. This gene is found on the X chromosome. The aim of this study was to analyze this SNP in a population of children with asthma and atopic dermatitis. In this study, 166 individuals, 79 adult controls (CTR) and 87 children with asthma (AA) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
1
26
1
4
Order By: Relevance
“…Another possible explanation for the inconsistency is the genetic heterogeneity of asthma and ethnicity/geometric difference, which suggests that the association between CYSLTR1 variations and asthma should be replicated in different populations. The results of the current meta-analysis using the present data and data from three previous reports [21,22,24] further support the genetic effect of SNP rs320995 on asthma.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Another possible explanation for the inconsistency is the genetic heterogeneity of asthma and ethnicity/geometric difference, which suggests that the association between CYSLTR1 variations and asthma should be replicated in different populations. The results of the current meta-analysis using the present data and data from three previous reports [21,22,24] further support the genetic effect of SNP rs320995 on asthma.…”
Section: Discussionsupporting
confidence: 67%
“…Although the associations between CYSLTR1 variations and asthma or asthma-related phenotypes have previously been investigated in Caucasian [21,23,24] and Asian populations [22,[25][26][27][28], the results were inconsistent. In detail, ARRIBA-MENDEZ et al [21] reported that the CYSLTR1 thymidine to cytosine substitution at nucleotide 927 (rs320995) variation could predispose male children to asthma and atopic dermatitis in a Caucasian population [21].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…For example, a link has been found between the silent SNP 102C/T of the 5-HT2A receptor gene in the temporal cortex and the pathogenesis of schizophrenia [31]. Jones and colleagues have shown that silent polymorphisms of the angiotensin-2 receptor increase cardiovascular risk in hypertension [32], while Arriba-Mendez and colleagues have found that when the C allele is present in the silent SNP 927T/C, male children may be predisposed to asthma and atopic dermatitis [33]. Similarly, a silent SNP, 988C→T of the Fas gene has been shown to have significant implications in the development of papillary thyroid carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%